Optimalisasi Aset Wakaf Tidak Bergerak dalam Pengembangan Pondok Pesantren: Studi Kasus di Pondok Pesantren Babul Khaer Kabupaten Bulukumba - Atikah Fauziyyah Amri; Putra, Trisno Wardy; Sirajuddin (Universitas Islam Negeri Alauddin Makassar, 2025)
This study analyzes the optimization of immovable waqf assets in the development of the Babul Khaer Islamic Boarding School in Bulukumba Regency. The purpose of the study is to identify efforts made by the Islamic boarding school in managing immovable waqf assets and analyze their impact on the development of the Islamic boarding school. This study uses a qualitative approach with a case study design. Data collection techniques were carried out through in-depth interviews, observations, and documentation studies. The results of the study indicate that optimization efforts were carried out through: (1) increasing the capacity of nazhir through waqf management training, (2) implementing digital platforms and periodic audits for transparency, (3) collaboration with Islamic Financial Institutions, and (4) intensive socialization to increase community participation. The impact of optimization is seen in three aspects of Islamic boarding school development: improving the quality of education through facility construction, improving the institution's reputation through accountable governance, and increasing community participation in supporting the waqf program. It is concluded that professional and collaborative waqf asset management is key to encouraging sustainable Islamic boarding school development.